Job dissatisfaction and migration: Evidence from Tajikistan - Ilhom Abdulloev (IZA Journal of Development and Migration, 2018)
Having a family member migrant reduces not only the labor force participation but also the job satisfaction of those left behind. Migrants' relatives build their expectations on earnings from migration through received information on the wage distribution in the destination country either from the size of remittances or directly from migrants. If their expected earnings from migration greatly exceed their current wages in the source country, migrant relatives become more dissatisfied with their jobs. Using a simple economic model of job satisfaction and applying both parametric and semiparametric estimations to Tajikistan's data, as well as with controlling for an endogeneity issue with the variable of interest, we estimate the significantly positive effect of the difference of the expected outside country earnings and current earnings of migrants' relatives on their job dissatisfaction. A larger gap between what an individual could earn in the migration destination country and what she receives now at her current job in the source country makes that individual unhappier.
Keywords: F22; F24; J28; O15; 330; Job satisfaction; Migration; Remittances; Tajikistan